Decreased serum levels of glycerol-3- phosphate dehydrogenase 1 and monoacylglycerol lipase act as diagnostic biomarkers for breast cancer - (:unkn) unknown (My University, 2021)
BACKGROUND: Breast cancer (BC) is one of the most life-threatening cancer types among women. Despite major developments in medical sciences and technologies, the incidence and mortality rates of BC cases are still increasing. One of the reasons for this increase is the absence of an easy to perform early-diagnostic tool. Although there are defined BC biomarkers routinely used for diagnostic and prognostic purposes, none of these biomarkers is useful for early diagnosis. Therefore, early diagnosis of BC remains an important challenge and there is a great need for the early-diagnostic biomarker(s). OBJECTIVE: In this study, we aimed to evaluate the diagnostic and prognostic values of glycerol-3-phosphate dehydrogenase (GPD1) and monoacylglycerol lipase (MAGL) proteins as non-invasive serum biomarkers. METHODS: GPD1 and MAGL serum levels were determined by ELISA for BC patients (n= 100) from five different subtypes, and healthy controls (n= 20), and a comparative analysis was performed to determine statistically significant expression differences among the groups. RESULTS: The results provided evidence that GPD1 acted as a diagnostic biomarker in distinguishing triple-negative breast cancer (TNBC) patients from other subtypes, and MAGL acted as a diagnostic biomarker in distinguishing healthy individuals from BC patients. CONCLUSION: GPD1 and MAGL might be proposed as non-invasive diagnostic biomarkers for BC with high sensitivity and specificity.
Keywords: Breast cancer; diagnostic biomarkers; ELISA; glycerol-3-phosphate dehydrogenase; monoacylglycerol lipase